Metaproteomics of anaerobic microbial communities degrading long-chain fatty acids - Salvador, A. F. (2013)
The anaerobic conversion of long-chain fatty acids (LCFA), and specifically the difference between the degradation of unsaturated- and saturated-LCFA, is not fully understood. In this work, syntrophic degradation of stearate (C18:0) and oleate (C18:1) was studied. A comparative metaproteomics approach, in which proteins were analyzed by LC-MS/MS, was combined with 16S rRNA gene pyrosequencing. Saturated- and unsaturated-LCFA were converted to methane by the anaerobic consortia. 16S rRNA gene pyrosequencing revealed differences in the microbial composition of sludges incubated with stearate and oleate, separately. Abundance of microorganisms within Deltaproteobacteria and within Synergistia taxa was higher in stearate and oleate incubations, respectively. Methanosaeta was the most abundant methanogen in both conditions. Metaproteomics results were similar and comparable distributions of COG functional categories were found for both samples. Archaeal proteomes were much better identified than bacterial ones, with five times more proteins retrieved. Most of the proteins identified belong to Methanosaeta concilli and Syntrophobacter fumaroxidans, two organisms that have their genome sequenced. Syntrophobacter belongs to Deltaproteobacteria, however this group was not dominant in oleate incubation as determined by pyrosequencing results. Studying metaproteomes of complex microbial communities is still a big challenge especially because most of the genomes are not sequenced which hinders protein identification.